A review of the Mutillidae (Hymenoptera) of Turkey - Lelej, Arkady S.; Yildirim, Erol (Zootaxa, 2009)
Sixty five species in 21 genera are recorded from Turkey. The new species, Skorikovia anatolica Lelej, sp. nov. (Turkey), is described and illustrated. The hitherto unknown male is recognized for Pseudophotopsis schachruda (Skorikov). A new synonymy is proposed for Pseudophotopsis schachruda (Skorikov 1935) = Ephutomma schachruda var. robusta Skorikov 1935, syn. nov., E. mavromoustakisi Suárez 1959, syn. nov. A new status is proposed for Krombeinella gaullei (Invrea). The status is resurrected for Pseudophotopsis schachruda (Skorikov) and Dentilla erronea (André). Nine species are recorded for the first time from Turkey: Pseudophotopsis syriaca (André), Myrmilla anopla Skorikov, Tropidotilla semirufa (André), Mutilla richterae Lelej, Skorikovia radoszkovskii (Skorikov), S. transcaucasica (Lelej), Smicromyrme azerbaidzhanicus Lelej, S. novaki Invrea, and S. rufipes (Fabricius). Krombeinella gaullei (Invrea) is recorded for the first time from Bulgaria. Eleven species and one subspecies are excluded from the list of Turkish fauna. A key to five Palaearctic species of Skorikovia is given. A tabular checklist for the mutillid fauna of Turkey, Greece, Armenia, Azerbaijan, and Georgia includes 106 species and four subspecies. A cluster analysis of faunal similarities among these countries for Mutillidae produce two major clusters (index similarity 0.4): Turkey and Greece (bootstrap probability 95 %), and Armenia, Azerbaijan, and Georgia (bootstrap probability 90 %), and demonstrates the important boundary between two large biogeographical subregions of Palaearctic: Mediterranean and Euro-Siberian. The Turkish fauna, especially its eastern part, is the transitional zone between these subregions. The mutillid fauna of Turkey consists of widely distributed in the Mediterranean (21), East Mediterranean (28), widely distributed in the Palaearctic (three) and Anatolian-Armenian (13) species, including five endemic species. The highest number of species is known from the Anatolian biogeographical province of Turkey: 55.